USING T-Z PLOTS AS A GRAPHICAL METHOD TO INFER LITHOLOGICAL VARIATIONS FROM GROWTH STRATA - Castelltort S.; Pochat S.; Van Den Driessche J. (My University, 2004)
The ’T–Z plot’ method consists of plotting the throw of sedimentary horizons across a growth fault versus their depth in the hanging wall. This method has been initially developed for the analysis of growth fault kinematics from seismic data. A brief analytical examination of such plots shows that they can also provide valuable information about the evolution of fault topography. When growth is a continuous process, stages of topography creation (fault scarp) and filling (of the space available in the hanging-wall) are related to non-dynamic (draping, mud-prone pelagic settling) and dynamic (sand-prone, dynamically deposited) sedimentation, respectively. In this case, the T–Z plot analysis becomes a powerful tool to predict major lithological variations on seismic profiles in faulted settings.
Keywords: Growth fault; Growth strata; Fault-generated topography; Fault kinematics; Net-to-gross ratio